Behavior of reinforced concrete beams strengthened with externally bonded hybrid fiber reinforced polymer systems - Hawileh, Rami A.; Rasheed, Hayder A.; Abdalla, Jamal A.; Al-Tamimi, Adil K. (My University, 2014)
This paper presents an experimental and an analytical investigation of the behavior of Reinforced Concrete (RC) beams strengthened in flexure by means of different combinations of externally bonded hybrid Glass and Carbon Fiber Reinforced Polymer (GFRP/CFRP) sheets. In order to obtain the mechanical properties of the hybrid sheets, multiple tensile coupon tests were conducted. In addition, an experimental program consisting of a control beam and four beams strengthened in flexure with GFRP, CFRP and hybrid FRP sheets was conducted. The series of the RC beams were tested under four point bending to study the flexural effectiveness of the proposed hybrid FRP sheets. The load–deflection response, strain readings at certain locations and associated failure modes of the tested specimens had been recorded. It is observed that the increase in the load capacity of the strengthened beams ranged from 30% to 98% of the un-strengthened control RC beam depending on the combination of the Carbon/Glass sheets. It was also observed that the ductility at failure loads of the beams strengthened with glass and hybrid sheets is higher than that with a single carbon sheet. Hence, the selection of the optimum combination of hybrid sheets can lead to a strengthening material which provides an improved ductility and strength in beam behavior. The load carrying capacity of the tested specimens was then predicted by the ACI 440.2R-08 guidelines. The predicted and measured results were in good agreement, within 5% for the control beam and for beams with one layer of strengthening sheet and between 13% and 17% for beams with two or more layers of hybrid strengthening sheets. Furthermore, an analytical model was developed to predict the load–deflection response of the tested specimens and the results were compared with the measured experimental data. The results showed that the developed analytical model predicted the response of the tested beam specimens with reasonable accuracy.
Keywords: Hybrid systems; Fiber Reinforced Polymer; Externally bonded sheets; Flexural strengthening; Carbon; Glass